Achieving superior nitrogen removal performance in low-strength ammonium wastewater treatment by cultivating concentrated, highly dispersive, and easily settleable granule sludge in a one-stage partial nitritation/anammox-HAP reactor. (15th July 2021) - Guo, Yan; Xie, Chenglei; Chen, Yujie; Urasaki, Kampachiro; Qin, Yu; Kubota, Kengo; Li, Yu-You
Highlights: Striking NRR of 1.28 kg/m 3 /d for low-strength wastewater treatment was achieved. Concentrated, highly dispersive and easily settleable sludge was cultivated in reactor. Tiny granules comprised of biomass and HAP were formed. Microbes were distributed in the outer layer of granule shell, while HAP in inner. This study enlightens one-stage PNA application in low-strength wastewater treatment. Abstract: In low-strength ammonium wastewater (LSAWW) treatment, the application of anammox-based process is still limited due to extreme instability and the poor nitrogen removal rate (NRR). In this work, granule sludge, comprised of functional microbes and hydroxyapatite (HAP), was inoculated and cultivated in a one-stage partial nitritation/anammox (PNA) reactor for LSAWW treatment. The results showed that at the hydraulic retention time (HRT) of about 1.0 h and the influent ammonium concentration of 63.0 mg/L, an average NRR of 1.28 kg/m 3 /d was achieved, which far exceeds that reported in similar studies. The main inorganic matter in sludge was identified as HAP through the X-ray diffractometer and Raman spectrum analysis. The tomographic images of wet granule created through computed tomography revealed that the interior density of the granules was uneven and many hollow structures existed in the granule interior. Combined with the Scanning Electron Microscope images of dry granules, it was found that the granules were comprised of hollow sub-granules. Since the biomass in the reactor increased with no obvious increase in the granule size, it was inferred that the hollow sub-granules had fragile connections with each other and that granules division occurred easily, resulting in the high dispersity of sludge. Florescence in situ hybridization results also showed that the ammonium-oxidizing bacteria and anammox bacteria were mainly distributed in the two sides of the sub-granule shells and the HAP in the middle. This kind of structure raised the density of granules and improved the settleability of sludge, which made it possible to achieve a high biomass in the reactor at a short HRT. Therefore, the sludge formed in the reactor was concentrated, highly dispersive and easily settleable. These factors appear to be crucial for achieving the desired nitrogen removal performance. This study marks a big leap in LSAWW treatment through the one-stage PNA process and has great potential in actual applications. Graphical abstract: Image, graphical abstract